2021
DOI: 10.3389/fped.2021.682078
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing a Research Agenda of Transitional Care Interventions for Childhood-Onset Disabilities

Abstract: Transitional care interventions have the potential to optimize continuity of care, improve health outcomes and enhance quality of life for adolescents and young adults living with chronic childhood-onset disabilities, including neurodevelopmental disorders, as they transition to adult health and social care services. The paucity of research in this area poses challenges in identifying and implementing interventions for research, evaluation and implementation. The purpose of this project was to advance this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Future interventions should continue to emphasize multidisciplinary transition clinics, social support, and caregiver engagement throughout this critical transition. New options to optimize health care utilization among young adults with disabilities include peer navigators [49] and youth stakeholder participation and shared decision making for youth-friendly health services [50].…”
Section: Table 1 Demographic and Health Characteristics Of Us Adolesc...mentioning
confidence: 99%
“…Future interventions should continue to emphasize multidisciplinary transition clinics, social support, and caregiver engagement throughout this critical transition. New options to optimize health care utilization among young adults with disabilities include peer navigators [49] and youth stakeholder participation and shared decision making for youth-friendly health services [50].…”
Section: Table 1 Demographic and Health Characteristics Of Us Adolesc...mentioning
confidence: 99%
“…CONNECT aims to be a web-based tool in peer-patient navigation for youth with childhood-acquired disabilities transitioning to adult health care and community services. The development of an evidence-based, patient and family–informed, web-based peer navigation intervention for young adults with childhood-onset disabilities holds the potential to improve transitional care experiences and outcomes [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transitioning adolescents and young adults (AYA) with childhood-onset conditions to adult medical care is challenging for multiple reasons. Adolescence is an important period of multiple changes, specifically as it relates to identity, education, and sexuality [ 5 ]. Having a chronic condition, such as sickle cell disease or chronic kidney disease (CKD), can complicate this developmental period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is an important period of multiple changes, specifically as it relates to identity, education, and sexuality [ 5 ]. Having a chronic condition, such as sickle cell disease or chronic kidney disease (CKD), can complicate this developmental period [ 5 ]. Studies among AYA with chronic health conditions have shown lower self-esteem and higher rates of depressive symptoms and suicidal thoughts [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%